Terminal Sliding Mode MPPT Control Algorithm Based on a Novel Switch Function - Wang, Xiangcheng; Dong, Na; Xiao, Wenwen (Chinese Control Conference, 2025)
The maximum power point tracking (MPPT) technology of photovoltaic power generation systems is crucial for ensuring the output efficiency and stability of the system. This study proposes a terminal sliding mode control strategy based on a novel switch function to address the shortcomings of traditional sliding mode control in photovoltaic maximum power point tracking technology, such as large tracking error and severe chattering phenomenon. This method is based on an independent photovoltaic power generation system equipped with Boost circuit. It introduces Sigmoid function as switching control to ensure the continuity of control change rate in time. An improved terminal sliding surface is designed to effectively reduce the chattering amplitude of traditional sliding mode control. Furthermore, it improves the system's steady-state accuracy and response speed to environmental changes, aiming to achieve maximum power tracking of photovoltaic output. To verify the superiority of the algorithm, a photovoltaic power generation system model was built for simulation experiments. The results show that under different lighting intensities, compared with traditional control algorithms, the terminal sliding mode control algorithm based on the proposed switching function can quickly achieve maximum power tracking and has strong robustness and stability.